The Political leader's motivating language use and his perceived effectiveness: The case of Narendra Modi's Mann Ki Baat. Issue 4 (11th October 2021) - Sharma, Daneshwar; Dubey, Akash D.
Abstract: The purpose of this article is to explain the usage of Motivating Language Theory (MLT) in the Indian PM Narendra Damodardas Modi's monthly radio address to the nation known as Mann Ki Baat ( Speech of Heart) . The various facets of motivating language (ML) used by the Indian Prime Minister are correlated with leader effectiveness. To study the relationship between three components of ML (i.e., direction giving, empathetic and meaning‐making language) and the followers' perception of leader's effectiveness, the ML scale and Leader Effectiveness scale were used in a survey. The structural equation modelling revealed that the theoretical framework that was constructed for this article had a reasonably good fit. This indicates that Modi has been using the ML (which comprises direction giving, empathetic, and meaning‐making language) to a very effective scale and thus increasing his leadership effectiveness. 摘要: 本文目的是分析印度总理纳伦德拉达摩达尔达斯莫迪在面向全国的每月广播讲话《心灵对话》中对激励性语言理论（MLT）的使用。印度总理对激励性语言（ML）的不同方面的使用，与领导者有效性（leader effectiveness）存在关联。为研究ML的三个组成部分（即方向指引、共情和意义建构）与追随者对领导者有效性的感知之间的关系，本文在一项调查中使用了ML量表（Mayfield et al, 1998）和领导者有效性量表（Nhavandi, 1991; Sharbrough, et al., 2006）。结构方程建模显示，本文所建构的理论框架是相当合适的。这表明莫迪一直以十分有效的方式使用ML（包括方向指引、共情和意义建构），并因此增加了他的领导力有效性。 Resumen: El propósito de este artículo es explicar el uso de la Teoría del Lenguaje Motivador (MLT) en el discurso de radio mensual del primer ministro indio Narendra Damodardas Modi a la nación conocida como Mann Ki Baat (Discurso del corazón). Las diversas facetas del lenguaje motivador (ML) utilizadas por el primer ministro indio están correlacionadas con la eficacia del líder. Para estudiar la relación entre tres componentes de ML (es decir, dar instrucciones, lenguaje empático y de creación de significado) y la percepción de los seguidores de la eficacia del líder, la escala ML (Mayfield et al,  1998) y la escala de eficacia del líder (Nhavandi, 1991; Sharbrough, et al., 2006) se utilizaron en una encuesta. El modelado de ecuaciones estructurales reveló que el marco teórico que se construyó para este artículo encajaba razonablemente bien. Esto indica que Modi ha estado usando el ML (que comprende un lenguaje de dirección, empatía y creación de significado) a una escala muy efectiva y, por lo tanto, ha aumentado la efectividad de su liderazgo.